2010
DOI: 10.1097/qad.0b013e32833a2b02
|View full text |Cite
|
Sign up to set email alerts
|

Abacavir and didanosine induce the interaction between human leukocytes and endothelial cells through Mac-1 upregulation

Abstract: Abacavir induces significant human leukocyte accumulation through the activation of Mac-1, which in turn interacts with its endothelial ligand ICAM-1. The fact that didanosine exhibits similar effects and that lamivudine and zidovudine do not points to a relationship between the chemical structure of NRTIs and the induction of leukocyte/endothelial cell interactions. This mechanism may be especially relevant to the progression of the vascular damage associated with atherosclerosis and myocardial infarction in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 35 publications
3
34
0
Order By: Relevance
“…Initiation of an ABC-containing ART was associated with smaller reductions in inflammatory markers than ART not containing ABC [90], although this is not a consistent finding across studies [91]. In vitro, ABC increases the adhesion of leukocytes to endothelial cells, through leucocyte activation [92] and also increased platelet reactivity through inhibition of soluble guanylyl cyclase [93]. These findings have also been confirmed in vivo.…”
Section: No Abacavirsupporting
confidence: 59%
“…Initiation of an ABC-containing ART was associated with smaller reductions in inflammatory markers than ART not containing ABC [90], although this is not a consistent finding across studies [91]. In vitro, ABC increases the adhesion of leukocytes to endothelial cells, through leucocyte activation [92] and also increased platelet reactivity through inhibition of soluble guanylyl cyclase [93]. These findings have also been confirmed in vivo.…”
Section: No Abacavirsupporting
confidence: 59%
“…Accumulation of these cells in the vessel wall is a hallmark of atherosclerosis and acute coronary syndrome, and is mediated by the interaction between adhesion molecules on endothelial and circulating cells. In an experimental system, Pablo et al recently demonstrated that ABC but not AZT or 3TC induced significant and dose-dependent increases in rolling flux and adhesion in the leukocyte-endothelium interaction [25]; these effects were blocked by antibodies against ICAM-1 or Mac-1. Furthermore, treatment of neutrophils and monocytes with ABC increased the expression of Mac-1, whereas no increases in ICAM-1, VCAM-1, or E-selectin were seen following the treatment of endothelial cells [25].…”
Section: Discussionmentioning
confidence: 99%
“…In an experimental system, Pablo et al recently demonstrated that ABC but not AZT or 3TC induced significant and dose-dependent increases in rolling flux and adhesion in the leukocyte-endothelium interaction [25]; these effects were blocked by antibodies against ICAM-1 or Mac-1. Furthermore, treatment of neutrophils and monocytes with ABC increased the expression of Mac-1, whereas no increases in ICAM-1, VCAM-1, or E-selectin were seen following the treatment of endothelial cells [25]. Altogether, these results suggest that ABC treatment could be linked to increased expression of Mac-1 rather than endothelial adhesion molecules, which would explain the paucity of positive results in studies of the latter.…”
Section: Discussionmentioning
confidence: 99%
“…ABC and ddI have been widely associated with a higher risk of cardiovascular events in HIV-infected patients [77,78], which has been confirmed by several in vitro studies [79]. However, the implication of mitochondrial dysfunction and oxidative stress in the induction of these effects is still unclear.…”
Section: Nucleoside Reverse Transcriptase Inhibitors (Nrti)mentioning
confidence: 95%